2017
DOI: 10.7205/milmed-d-16-00387
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Point-of-Care Versus Laboratory Troponin Testing in an Emergency Department Setting

Abstract: Background: There have been concerns regarding troponin results accuracy between point-of-care (POC) testing preformed in an emergency department (ED) setting and laboratory testing. The purpose of this study was to compare the results of cardiac troponin I testing as concerns POC testing and laboratory analysis as a way to show that these results are interchangeable. Methods: A retrospective chart review was performed from October 2012 through September 2013 to identify all patients who presented to the ED th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The POCT system is the appropriate way of test for rapid evaluation of patient presenting with acute coronary syndrome (Juliano & Wason 2017). According to the results, it is proven that HUBI-QUANPro troponin I was able to provide result at ~15 minutes interval which meets the POCT advantages of providing cardiac troponin result at shorter interval that has potential in improving the acute patient care and enabling rapid clinical decision.…”
Section: Discussionmentioning
confidence: 93%
“…The POCT system is the appropriate way of test for rapid evaluation of patient presenting with acute coronary syndrome (Juliano & Wason 2017). According to the results, it is proven that HUBI-QUANPro troponin I was able to provide result at ~15 minutes interval which meets the POCT advantages of providing cardiac troponin result at shorter interval that has potential in improving the acute patient care and enabling rapid clinical decision.…”
Section: Discussionmentioning
confidence: 93%
“… 38 Others showed the practical utility of POC cTn for patients presenting to the emergency department. 39 , 40 Japanese authors recently assessed the usefulness of POC cTn in the emergency department. 41 A POC study conducted in an emergency department in Taiwan demonstrated the advantages of using multiple cardiac biomarkers to improve diagnosis of elderly and female patients, 42 challenging groups for diagnosis, who would benefit in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion samples and smears can likewise provide clinically essential information; widely used guaiac-based stool-blood tests allow instant detection of fecal occult blood in human stool (e.g. in patients presenting to the ED with anemia of unknown origin) [13][14][15][16][17]. Nasopharyngeal specimens can be examined for the presence of Influenza A and B virus nucleoprotein antigens [18], respiratory syncytial fusion protein or Streptococcus pyogenes group A antigens within minutes.…”
Section: Rapid Diagnostic Testing and Point-of-carementioning
confidence: 99%
“…A score of ≥3 points has a high specificity (98%), but low sensitivity for the presence of myocardial infarction [15,16]. The modified method according to Smith et al uses a ST/S ratio of >0.25 as an equivalent for excessive discordance (Sgarbossa's criterion C, see above), which further improves diagnostic precision [21].…”
Section: Electrocardiogrammentioning
confidence: 99%